Wearable Devices: Wearable Microfluidic Diaphragm Pressure Sensor for Health and Tactile Touch Monitoring (Adv. Mater. 39/2017). Issue 39 (13th October 2017) - Gao, Yuji; Ota, Hiroki; Schaler, Ethan W.; Chen, Kevin; Zhao, Allan; Gao, Wei; Fahad, Hossain M.; Leng, Yonggang; Zheng, Anzong; Xiong, Furui; Zhang, Chuchu; Tai, Li‐Chia; et al.
Abstract : A flexible microfluidic diaphragm pressure sensor using liquid‐metal microchannels is presented by Ali Javey and co‐workers in article number1701985 . The sensor is capable of detecting pressures less than 100 Pa with a resolution of less than 50 Pa. Both heart‐rate monitoring and tactile pressure mapping of a glove with multiple embedded sensors are demonstrated.